Hemoperfusion with polymyxin B-immobilized fiber column improves liver function after ischemia-reperfusion injury - Sato, Hiroaki (The WJG Press and Baishideng, 2009)
AIM: To investigate the usefulness of direct hemoperfusion with a polymyxin B-immobilized fiber column (DHP-PMX therapy) for warm hepatic ischemia-reperfusion (I/R) injury after total hepatic vascular exclusion (THVE) using a porcine model. METHODS: Eleven Mexican hairless pigs weighing 22-38 kg were subjected to THVE for 120 min and then observed for 360 min. The animals were divided into two groups randomly: the DHP-PMX group (n = 5) underwent DHP-PMX at a flow rate of 80 mL/min for 120 min (beginning 10 min before reperfusion), while the control group did not (n = 6). The rate pressure product (RPP): heart rate × end-systolic arterial blood pressure, hepatic tissue blood flow (HTBF), portal vein blood flow (PVBF), and serum aspartate aminotransferase (AST) levels were compared between the two groups. RESULTS: RPP and HTBF were significantly (P < 0.05) higher in the DHP-PMX group than in the control group 240 and 360 min after reperfusion. PVBF in the DHP-PMX group was maintained at about 70% of the flow before ischemia and differed significantly (P < 0.05) compared to the control group 360 min after reperfusion. The serum AST increased gradually after reperfusion in both groups, but the AST was significantly (P < 0.05) lower in the DHP-PMX group 360 min after reperfusion. CONCLUSION: DHP-PMX therapy reduced the hepatic warm I/R injury caused by THVE in a porcine model.